Question about SoftMath Algebrator - Algebra Homework Solver (689076614429)

Go through the expression replacing each letter symbol by its value then perform the operations

3*(-2)-2*(-1)+(3*0)=-6+2+0=-4

Posted on Oct 18, 2013

-1 (negative one).

If this is homework, be sure to show your work.

Posted on Apr 30, 2013

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

goodluck!

Posted on Jan 02, 2017

no we can not .

May 09, 2016 | Texas Instruments TI-Nspire CX CAS...

Add a graph .

In Documents Toolbox, select 3: Graph/Entry Edit

Unfold the menu and select Equation (not function). Enter your equation.

For the 3D part, I am afraid you will have to read the manual.

In Documents Toolbox, select 3: Graph/Entry Edit

Unfold the menu and select Equation (not function). Enter your equation.

For the 3D part, I am afraid you will have to read the manual.

Jan 22, 2016 | Texas Instruments TI-Nspire CX CAS...

This is best written as two separate equations:

8x+3y = -23 and 34x+ 5y = -23

Solving the first one for x:

8x = -23-3y

x = -23/8 - 3/8y

Substituting this value for x into the second equation:

34(-23/8 - 3/8y) + 5y = -23

-97.75 - (34)(.375)y + 5y = -23

-97.75 - 12.75y + 5y = -23

-97.75 -7.75y = -23

-7.75y = 97.75-23=74.75

**y **= -74.75/7.75 =** -9.645161**

Substitution back into the equation for x:

x = -23/8 - 3/8(-9.645161)

x = -2.875 + 3.616935

**x** **=.741935**

8x+3y = -23 and 34x+ 5y = -23

Solving the first one for x:

8x = -23-3y

x = -23/8 - 3/8y

Substituting this value for x into the second equation:

34(-23/8 - 3/8y) + 5y = -23

-97.75 - (34)(.375)y + 5y = -23

-97.75 - 12.75y + 5y = -23

-97.75 -7.75y = -23

-7.75y = 97.75-23=74.75

Substitution back into the equation for x:

x = -23/8 - 3/8(-9.645161)

x = -2.875 + 3.616935

Dec 12, 2014 | Bagatrix Algebra Solved! 2005 (105101) for...

(-9/3)x=-2

First simplify -9/3 to -3 : -3x=-2

Divide by -3.

x=-2/-3=2/3

First simplify -9/3 to -3 : -3x=-2

Divide by -3.

x=-2/-3=2/3

Oct 24, 2013 | Office Equipment & Supplies

This equation doesn't have whole number factors so you have to solve it by completing the square or using the quadratic equation. I used the quadratic equation and got the following answers.

[3 + sqrt(209)]/10 and [3 - sqrt(209)]/10

I hope this helps you out.

[3 + sqrt(209)]/10 and [3 - sqrt(209)]/10

I hope this helps you out.

Jul 05, 2011 | SoftMath Algebrator - Algebra Homework...

(a ± b)³ = a³ ± 3a²b + 3ab² ± b³

(a ± b)4 = a4 ± 4a³b + 6a²b² ± 4ab³ + b4

a² - b² = (a - b)(a + b)

a² + b² = (a - bi)(a + bi)

a³ - b³ = (a - b)(a² + ab + b²)

a³ + b³ = (a + b)(a² - ab + b²)

a4 + b4 = (a² + 2½ab + b²)(a² - 2½ab + b²)

an - bn = (a - b)(an-1 + an-2b + ... + bn-1), for n even

an + bn = (a + b)(an-1 - an-2b - ... - bn-1), for n odd

Jun 19, 2011 | Computers & Internet

Fred = Mary +3

7*mary = 6/7 *Fred

substitute fred =mary + 3

7m = 6/7 * (mary + 3) 7m = 6/7*m + 6/7*3 7m - 6/7*m = 6/7*3 m(7-6/7)= 6/7*3

m = (6/7*3) / (7-6/7) m=0.419 years old

substitue m into fred = mary+3 Fred = 3.419 Years old

7*mary = 6/7 *Fred

substitute fred =mary + 3

7m = 6/7 * (mary + 3) 7m = 6/7*m + 6/7*3 7m - 6/7*m = 6/7*3 m(7-6/7)= 6/7*3

m = (6/7*3) / (7-6/7) m=0.419 years old

substitue m into fred = mary+3 Fred = 3.419 Years old

Jun 08, 2011 | Computers & Internet

this is a simple algebraic equation in which we have to calculate the value of 'x' using simple operations

7+(9-5x)=5(2-x)

step 1(pen the brackets) 7+9-5x=10-5x

step 2(add 7 and 9) 16-5x=10-5x

now as 5x gets cancelled both the sides of the equal sign therefore no solution of this algebraic equation exist.

7+(9-5x)=5(2-x)

step 1(pen the brackets) 7+9-5x=10-5x

step 2(add 7 and 9) 16-5x=10-5x

now as 5x gets cancelled both the sides of the equal sign therefore no solution of this algebraic equation exist.

Mar 24, 2011 | MathRescue Word Problems Of Algebra Lite

Hello,

The Casio FX-300ES does not handle symbolic algebra. So it cannot factor a general polynomial expression. The methods can be found in any book on Algebra.

However if you are interested in approximate factorization of quadratic and cubic polynomials, you can use the calculator to do that. It can solve aX^3 +bX^2+cX+d =0 and the quadratic equations.

If you want to factor a cubic polynomial P3(X) = aX^3+bX^2+cX+d , you write the corresponding cubic equation as**aX^3+bX^2+cX=d =0** , then you divide all terms of the equation by** a** to obtain

**X^3+(b/a)X^2+(c/a)X+(d/a)=0.**

You use the calculator to solve (approximately) this equation.

Suppose you find the 3 roots**X1,X2,and X3.** Then the polynomial X^3+(b/a)X^2+(c/a)X+(d/a) can be cast in the factored form (X-X1)(X-X2)(X-X3) and the original polynomial P3(X) can be written as

**P3(X) = a*(X-X1)(X-X2)(X-X3) **

You can handle the quadratic polynomial the same way.

P2(X) =a*(X-X1)(X-X2) where X1, X2 are the two real roots

Hope it helps.

The Casio FX-300ES does not handle symbolic algebra. So it cannot factor a general polynomial expression. The methods can be found in any book on Algebra.

However if you are interested in approximate factorization of quadratic and cubic polynomials, you can use the calculator to do that. It can solve aX^3 +bX^2+cX+d =0 and the quadratic equations.

If you want to factor a cubic polynomial P3(X) = aX^3+bX^2+cX+d , you write the corresponding cubic equation as

You use the calculator to solve (approximately) this equation.

Suppose you find the 3 roots

You can handle the quadratic polynomial the same way.

P2(X) =a*(X-X1)(X-X2) where X1, X2 are the two real roots

Hope it helps.

Sep 27, 2009 | Casio fx-300ES Calculator

154 people viewed this question

Usually answered in minutes!

×